Estimates of global burden of snakebite: A literature review and geostatistical modelling study - Dileepa Senajith Ediriweera; Anuradhani Kasturiratne; Arunasalam Pathmeswaran; Ymkje Stienstra; Gerardo Martín; Takuya Iwamura; Kris A. Murray; Hithanadura Janaka de Silva; Peter John Diggle; David Griffith Lalloo (PLOS Medicine, 2026)
Background Snake envenoming (SE) remains an important public health problem, disproportionately affecting impoverished rural communities in tropical and subtropical regions. Although previous attempts have been made to quantify the global burden of SE, accurate, up-to-date data remain scarce. Here we present a comprehensive re-evaluation of the global burden of snakebite, 17 years after our initial estimate. Methods and findings A new literature review was conducted on snakebites, SE and mortality published in any language, up to March 31, 2025, to update the knowledge accumulated since our first global burden estimate. Based on country- and region-level aggregated data, and hospital and community-based survey data, we modelled SE and mortality burden in relation to geographic location. Explanatory variables were selected to reflect the underlying social and natural environmental conditions. Low and high estimates of the global snakebite burden were calculated using geostatistical models that produced individual-country estimates, accounting for possible underreporting of data when appropriate. We estimate that at least 2.1 million envenomings and 274,000 deaths occur globally each year due to snakebites, and our high estimates suggest up to 7 million envenomings and 513,000 deaths annually. Low-income countries exhibit the highest incidence and mortality rates, with sub-Saharan Africa accounting for 45% of global envenomings and deaths, nearly three times the incidence observed in South Asia. These estimates suggest that previous burden estimates could substantially underestimate the scale of the problem. The main limitations of this study are the scarcity and heterogeneity of empirical data in many countries and the reliance on modelling assumptions to estimate burden in settings with limited or no direct observations. Conclusions Snake envenoming is a significant cause of morbidity and mortality globally, with sub-Saharan Africa, South Asia, and Southeast Asia being the most severely affected regions. Further improvement in the quality of epidemiological data is required for more accurate estimates of the global burden, particularly in sub-Saharan Africa.